CO2 monitoring to assess ventilation rate: practical suggestions from a laboratory study - Zhang, Dadi; Ding, Er; Bluyssen , Philomena M. (CLIMA 2022 conference, 2022)
Several recent studies have demonstrated that ventilation plays an important role in the transmission of SARS-CoV-2 (the coronavirus that causes COVID-19) in public buildings, such as schools. However, there are no clear rules on how to assess the ventilation performance in classrooms, especially during a pandemic. Therefore, the main objective of this study was to develop guidance to assess the ventilation performance under different ventilation regimes. A full-scale laboratory study was conducted in the Experience room of the SenseLab, where CO2 concentrations were monitored at 19 locations (18 indoors and one outdoors) simultaneously and recorded every 30 seconds by HOBO® CO2 loggers. The experiment was conducted under four different ventilation regimes: ‘600 m3/h mixing’, ‘open windows’, ‘no ventilation’, and ‘open windows and door’. Each regime lasted 50 minutes, which is approximately the duration of one normal lesson at Dutch secondary schools. Six (three males and three females) healthy subjects were invited to participate in this experiment as CO2 sources. Results showed that CO2 concentrations varied significantly between different measurement locations in the same classroom, especially under natural ventilation conditions. This demonstrates the need of monitoring the CO2 concentration, next to outdoors, at more than one location in a classroom. The finding of this study could contribute to a standardized way of monitoring CO2 concentrations and the assessment of ventilation performance of an occupied space.